Legal mechanism of cross collateral guarantee execution in credit agreements in Indonesia - Mahmud, Nur Rahmawati (Journal of Law Science, 2024)
The purpose of this research is to examine and contrast the two methods of conventional and cross-collateral execution in Indonesian credit agreements. Using a descriptive-analytical methodology grounded on normative law, this paper examines pertinent rules including the Mortgage Law and the Fiduciary Guarantee Law. According to this study's findings, even though the legislative framework has laid the groundwork for creditor protection, cross-collateral execution often encounters difficulties due to the inadequate execution methods and priority order of creditor claims. The most pressing issue is the possibility for conflicts to arise due to the lack of clarity about the relative importance of creditors' rights. Here, a less complicated method of execution is required to reduce the likelihood of disputes. Among the many suggestions made by this research are changes to the legislation to make priority rights of creditors more clear, improvements to the collateral registration system, and the use of blockchain technology to make the collateral registration and execution process more transparent. As a result, this research adds to the body of knowledge on Indonesian collateral law and provides useful guidance for resolving issues with cross-collateral collateral execution.